Fracture toughness testing of geomaterials using semicircular specimen - Kuruppu, Mahinda (2018)
© 2018 ISRM International Symposium 2000, IS 2000. All rights reserved. Fracture mechanics is primarily used to predict the failure of structures made of engineering materials. Principles of fracture mechanics are applicable for improving the strength and stability of mine structures. However, fracturing is considered to be favourable in certain other applications such as blasting and comminution in mining and mineral processing. Fracture properties such as fracture toughness are useful for the fracture characterisation of a material irrespective of the type of application. Mode I fracture toughness is a material property that is related to the critical stress intensity factor in the crack opening mode. In this investigation, semi-circular bend test specimens having a chevron notch are used to determine the fracture toughness. The relationship between the stress intensity factor and crack length is determined using the finite element method. The fracture toughness is shown to correspond to the minimum level of the stress intensity factor associated with crack extension. Fracture toughness is evaluated in a number of rock types using the experimentally determined fracture load and the normalised stress intensity factor.